Effect of sodium dodecylbenzene sulphonate modifier and PP-g-MA on the morphology and thermal conductivity of PP/EG composites. (26th November 2017) - Mukwada, Lesley Tsitsi; Mochane, Mokgaotsa Jonas; Motaung, Tshwafo Elias; Motloung, Setumo Victor; Koao, Lehlohonolo Fortune
ABSTRACT: This study investigates the influence of expanded graphite (EG) and sodium dodecylbenzene sulfonate (SDBS) treated EG (SDBS/EG) on the structure, thermal stability and thermal conductivity of polypropylene (PP) and polypropylene/maleic anhydride-grafted polypropylene (PP/MAPP) blend. The dispersion of EG and SDBS/EG was characterized by scanning electron microscopy (SEM). The SDBS-EG showed a crushed and randomly deformed structure. There was an improved interfacial adhesion between the polymer and the SBDS-EG particles. The graphite dispersed much better with less restacking for PP/MAPP/SDBS/EG system. The better dispersion also contributed towards the improved compatibility between the PP or PP/MAPP and SBDS/EG. The SDBS functionalised EG composites showed better thermal stability than the non-functionalized SDBS composites. It was further shown that the functionalized graphite significantly improved the thermal conductivity of the PP and PP/MAPP. This is because the functionalized SDBS/EG seemed to improve the interfacial heat transfer between the conductive filler (EG) and PP matrix.